3D Simulation of acoustic waves propagating through porous domain using PUFEM tetrahedral elements. (August 2020) - Yang, Mingming; Breard, Cyrille; Cen, Yipeng; Chazot, Jean-Daniel
Abstract: Partition of Unity Finite Element Method is one of the new deterministic prediction techniques developed for tackling medium and high frequency wave problems, because it has the overwhelming advantage over traditional Finite Element Method due to its high efficiency and low computational cost properties. In this paper, PUFEM is further developed to simulate the 3D sound pressure field where porous material is included and modeled as an equivalent homogeneous fluid. Lagrange multipliers are applied at the air and porous material interface. The performance and efficiency of the established numerical model using 3D PUFEM elements are analyzed, it is shown that PUFEM technique can effectively reduce the computational burden while still maintaining the sufficient accuracy for the simulation results of 3D acoustic problems.